Pelatihan Tech for Kids Memperkenalkan STEM untuk Mengembangkan Kemampuan Kepemimpinan Siswa di Era Industri 4.0 - Deny Nusyirwan; Eko Prayetno; Sapta Nugraha; Harits Aditya Nugraha; Muhammad Andika; Muhammad Abyan Fadillah (Jurnal Surya Masyarakat, 2020)
The industry is currently undergoing a transformation towards full digitization and intelligence of the manufacturing process, which is called the Fourth Industrial Revolution or Industry 4.0. Visionary but fairly realistic concepts such as Internet of Things, Cloud-based Manufacturing and Smart Manufacturing applications. Although there is mutual agreement on the need for advancement in production technology and business models in the Industry 4.0 sense, the main obstacle lies in the perception of complexity and abstractness which partially hinders its rapid transformation into industrial practice. The term "STEM education" refers to teaching and learning in the fields of science, technology, engineering and mathematics. Usually includes educational activities at all grade levels starting from the period before entering school to higher education, from formal arrangements in the classroom to informal such as after school programs. Student leadership means students take an active role in their education and develop positive skills in the process. The goal of inspiring student leaders is to create a culture of ownership and collaboration. Student leadership development helps create skills that students can carry into adulthood. With this background, community service activities were carried out by providing STEM skills training to foster the leadership of the students of Madrasah Ibtidaiyah Raudhatul Qur'an Tanjungpinang in preparing for the era of the industrial revolution 4.0. This training is also known as Tech for Kids.